”DOLO-DOLO” SEBAGAI BENTUK MUSIK, TARI DAN SASTRA MASYARAKAT FLORES TIMUR (LAMAHOLOT), NTT - Maria Klara Amarilis Citra Sinta Dewi Tukan (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
: Dolo-dolo as a Kind of Music, Dance and Literary Community in East Flores (Lamaholot), NTT. Dolo-dolo is a kind of folk art that consist of music, dance and literature that comes from the East Flores (Lamaholot), NTT. There are many other similar arts can be found in every province from NTT that has the same elements. The art like this usually have the shape of ritual and entertainment by the performance art. Dolo-dolo is a kind of art from NTT that packaged in one complete presentation which has third of the art elements in a show. Such as in the form of dance, which is not only the dance that contained in the serving, but rather the elements of music and literature also very important in it. Based on its history and its development, Dolo-dolo has value and functionality in the local area connection that does not even have separated from Western culture. This became the basis of a mix of acculturation and inculturation are very complete.